The Pentahelix Strategy for Addressing Radicalism and Terrorism Issue in Surabaya - Wibowo, Prihandono; Hapsari, Renitha Dwi; Ascha, Muchammad Chasif (Nusantara Science and Technology Proceedings, 2023)
Over the past few decades, Surabaya has maintained a reputation as a city with a high level of safety. The capital of East Java Province is devoid of any socio-political upheaval. During the 2000s, some major cities, including Jakarta and Bali, saw a wave of terrorism. However, it is noteworthy that the city under consideration, often called the "city of heroes," did not see comparable tragedies during this period. In the year 2018, Surabaya encountered a terrorist occurrence. The phenomena of radicalism and terrorism are intricate and multifaceted, necessitating the involvement of multiple stakeholders for their resolution. The Surabaya municipal government emphasizes fostering collaboration among various stakeholders to ensure stability. Nevertheless, the provincial capital of Jawa Timur continues to experience many occurrences, such as the recent surge in terrorist apprehensions in Surabaya and the prevailing existence of extremist factions. Evidence suggests the presence of radical movements within the city of Surabaya. The primary objective of this study is to examine the implementation of cross-sectoral collaboration in addressing issues related to radicalism and terrorism within the urban context of Surabaya. This research aims to provide valuable insights for the Surabaya city government and relevant stakeholders regarding the issue of radicalism and terrorism in Surabaya to inform policy decisions. Within the framework of radicalism and terrorism, it is vital to explore how cross-sector collaboration in the urban setting of Surabaya addresses this phenomenon. This study uses the Penthaelix cooperation framework to analyze the dynamics of collaboration among various stakeholders in Surabaya City in their efforts to combat radicalism and terrorism. The researchers successfully identified eight key informants representing each stakeholder cluster. Through conducting research and engaging in interviews, valuable insights were gathered regarding the patterns of cooperation that emerged and the problems encountered.